Implementasi Kompres Hangat Dalam Menurunkan Intensitas Nyeri Pada Lansia Dengan Arthritis Gout (Study Kasus): IMPLEMENTATION OF WARM COMPRESSES TO REDUCE PAIN INTENSITY IN ELDERLY PEOPLE WITH GOUTY ARTHRITIS (CASE STUDY) - Palupi Dewi Lestari; swito prastiwi; Rossyana Septyasih (Poltekkes Kemenkes Malang, 2024)
Gout arthritis causes many complaints, especially among the elderly, such as joint pain. Gout pain is caused by a buildup of uric acid crystals in the joints. It is hoped that non-pharmacological warm compress therapy can be an alternative in reducing joint pain in gout sufferers. This research uses a descriptive case study method with 2 research subjects on February 26 2024-March 10 2024. Data collection uses structured observation and interview techniques and is presented in the form of tables, graphs and narratives. The research results for subject 1 before applying a warm compress showed pain intensity on a scale of 6 (much more grimacing) and subject 2 obtained a scale of 6 (much more grinning). Meanwhile, after applying a warm compress to subject 2, the result was scale 2 (flat face) and subject 2 received scale 4 (slightly grinning). Recommendations for further research include choosing a different gender of research subjects so that the differences in pain intensity felt between men and women can be known and giving warm compresses for longer periods so that the results of the development of research subjects' pain intensity are maximized.